Resistance to Antibiotics in Thermophilic Campylobacters - Aleksić, Ema; Miljković-Selimović, Biljana; Tambur, Zoran; Aleksić, Nikola; Biočanin, Vladimir; Avramov, Stevan (Frontiers in Medicine, 2021)
Campylobacter jejuni (C. jejuni) is one of the most frequent causes of bacterial enterocolitis globally. The disease in human is usually self-limiting, but when complications arise antibiotic therapy is required at a time when resistance to antibiotics is increasing worldwide. Mechanisms of antibiotic resistance in bacteria are diverse depending on antibiotic type and usage and include: enzymatic destruction or drug inactivation; alteration of the target enzyme; alteration of cell membrane permeability; alteration of ribosome structure and alteration of the metabolic pathway(s). Resistance of Campylobacter spp. to antibiotics, especially fluoroquinolones is now a major public health problem in developed and developing countries. In this review the mechanisms of resistance to fluoroquinolones, macrolides, tetracycline, aminoglycoside and the role of integrons in resistance of Campylobacter (especially at the molecular level) are discussed, as well as the mechanisms of resistance to β-lactam antibiotics, sulphonamides and trimethoprim. Multiple drug resistance is an increasing problem for treatment of campylobacter infections and emergence of resistant strains and resistance are important One Health issues.